A Review on Data Fusion and Integration - Roja, T; Kumar, A. Murali Mohan (International Journal of Computer Sciences and Engineering, 2025)
A standout amongst the most critical and valuable element of independent versatile robots is their capacity to receive themselves to work in unstructured condition. Today robots are performing self-sufficiently in mechanical conditions, and in addition in swarmed open places. The essential necessity of a clever portable robot is to create and keep up confinement and mapping parameters to finish the unpredictable missions. In such circumstances, a few difficulties emerge because of the errors and vulnerabilities in sensor estimations. Different systems are there to deal with such commotions where the multi sensor information combination isn't the remarkable one. Amid the last two decades, multi sensor information combinations in versatile robots turn into a prevailing worldview because of its potential favorable circumstances like decrease in vulnerability, increment in precision, and decrease of cost. This paper exhibits the detail survey of multi sensor information combination and its applications for self-ruling versatile.